Main contributors to the baseball bat head speed considering the generating factor of motion-dependent term - Koike, S.; Mimura, K. (Procedia Engineering, 2016)
Motion-dependent term (MDT), which consists of centrifugal force, Coriolis force and gyro moment expressed in the equation of motion for a multi-link system, plays significant roles in the generation of tip speed in a high speed swing motion. A phenomenon caused by the MDT is usually called as "whip-like effect" and "kinetic chain". Since the baseball batting is one of high speed swing motion manipulating a bat by both hands, it is important to make clear the generating factor of MDT and main contributors to the generation of bat head speed. The purpose of this study was to quantify main contributors to the bat head speed considering the generating factor of MDT. The whole-body segments with bat were modelled as a system of sixteen-rigid linked segments. The equation of motion for the system was obtained by considering anatomical constraint axes at joints and modelling errors. A recurrence formula with respect to the generalized velocity vector consisting of linear and angular velocity vectors of all segments was derived. Five collegiate baseball players, participated as subjects, hit a teed ball as strong as possible. The kinematic and kinetic data were measured with the motion capture system with 3 force platforms and an instrumented bat. The results indicates that the abduction and extension torques at the knob-side shoulder joint and the forward rotation torque at the torso joint are the main positive contributors to the generation of bat head speed among the participants.